Citizenship Utopias in the Global South: The Emergent Forms of Activism in an Era of Disillusionment - Henri Onodera; Martta Kaskinen; Eija Ranta (Routledge, 2025)
Citizenship Utopias in the Global South is an edited collection of empirical research that explores emergent forms of activism in Africa, Asia, and Latin America in times of multiple crises. At the intersection of hope and disillusionment, the diverse and thought-provoking chapters investigate emerging forms of activism in the Global South – including youth activisms, anti-racism struggles, feminist initiatives, online dissent, and Indigenous movements. In the 2020s, many parts of the world are witnessing contradictory processes of popular claims to rights, livelihoods, and social justice, and subsequent forms of populist authoritarianism and the securitization of civil society. Previously hopeful calls for dignity, democracy, and social justice – through protesting, strikes, civil society campaigns, legal reforms, and elections, for example – have been met with disdain and civic disengagement. This book investigates the re-imagination and pursuit of citizen activism in such times of popular disillusionment. It explores citizenship utopias as social imaginaries that are enacted and that articulate an ideal social order or democratic polity with ideal forms of experiencing citizenship. Its chapters interrogate conventional approaches to citizenship by introducing a nuanced and empirically grounded exploration of the complex ways in which people experience, negotiate, and engage in the societal changes that they aspire towards. The examination of citizenship utopias outlines contemporary signals for transformative futures and their possibilities. The book undertakes a fresh effort at contributing to the shifting terrain of critical development studies, political anthropology, political sociology, and decolonising scholarship by engaging in discussions about citizenship, activism, disillusionment, and future societal alternatives in times of multiple global challenges.
Keywords: 300; activism; citizenship; utopias; disillusionment; politics; democracy; decolonization; decolonisation; social movements; civil society; Global South; sociology; state formation; political sociology